Reclassification of the taxonomic status of SEMIA3007 isolated in Mexico B-11A Mex as Rhizobium leguminosarum bv. viceae by bioinformatic tools - Kishi, Luciano Takeshi [UNESP]; Fernandes, Camila Cesário [UNESP]; Omori, Wellington Pine [UNESP]; Campanharo, João Carlos [UNESP]; De Macedo Lemos, Eliana Gertrudes de Macedo [UNESP] (Springer Nature, 2016)
Background: Evidence based on genomic sequences is extremely important to confirm the phylogenetic relationships within the Rhizobium group. SEMIA3007 was analyzed within the Mesorhizobium groups to define the underlying causes of taxonomic identification. We previously used biochemical tests and phenotypic taxonomic methods to identify bacteria, which can lead to erroneous classification. An improved understanding of bacterial strains such as the Mesorhizobium genus would increase our knowledge of classification and evolution of these species. Results: In this study, we sequenced the complete genome of SEMIA3007 and compared it with five other Mesorhizobium and two Rhizobium genomes. The genomes of isolated SEMIA3007 showed several orthologs with M. huakuii, M. erdmanii and M. loti. We identified SEMIA3007 as a Mesorhizobium by comparing the 16S rRNA gene and the complete genome. Conclusion: Our ortholog, 16S rRNA gene and average nucleotide identity values (ANI) analysis all demonstrate SEMIA3007 is not Rhizobium leguminosarum bv. viceae. The results of the phylogenetic analysis clearly show SEMIA3007 is part of the Mesorhizobium group and suggest a reclassification is warranted.
Keywords: Comparative analysis; Core genome; Genome sequencing; Ortholog genes; Phylogenetic analysis